International E-Banking:: ICT Investments and the Basel Accord - Lin, Hong-Jen; Lin, Winston (Journal of Comparative International Management, 2007)
This study investigates how the Basel Accord and Information and Telecommunications Technologies (ICT) investments affect the commercial banking industries across countries. We employ the stochastic frontier approach to explore a data set composed of commercial banks from 51 countries. We find that telecommunications investment reduces, and the Basel Accord proxy enhances, the cost efficiency of commercial banks under study. Moreover, it is found that ICT investments improve cost efficiencies of commercial banks for countries in which the regulations are consistent with the international supervision.